PANCASILA ANTARA AKUMULASI INFORMASI DAN PARADIGMA KEBANGSAAN - Toni Toni; Faisal Faisal (Fakultas Hukum Universitas Bangka Belitung, 2019)
Pancasila in relation to the law always has a general tendency that Pancasila is placed as the highest part of the Indonesian legal pyramid model. Pancasila becomes contemplation, concerning efforts to put Pancasila at a standstill in accumulating information or continuing it as a national paradigm and if Pancasila is expected to shape the nation's way of thinking, then it should be like what we are behaving in a national context. in fact, Pancasila is an authentic feeling of the national paradigm which must be continually maintained and pass on those values to logical consciousness with intuitive reflection.